Profil Kesesuaian Penulisan Resep Pada Pasien Umum Eawat Inap Dengan Formularium Di Rumah Sakit Bedah Mitra Sehat Lamongan - Nasyanka, Anindi Lupita; Maesaroh, Dewi; Arizka, Hawwin Elina (Universitas Muhammadiyah Gresik, 2020)
The hospital minimum service standard becomes the minimum reference for assessing the services provided by the hospital. One important point is the suitability of prescribing to patients based on hospital formulary. In this study aims to determine the suitability profile of inpatient prescribing in Rumah Sakit Bedah Mitra Sehat Lamongan with hospital formulary. The research method used was cross-sectional with accidental sampling as many as 614 prescriptions from May until June 2019. The results showed that the percentage of compliance with the average prescribing in May-June did not reach the minimum service standards (100%). therefore, a periodic evaluation of the formulary and outreach is needed to all doctors who write prescriptions for inpatients Keyword : prescribing, hospital formulary, inpatient